Cancer Care in Pandemic Times: Building Inclusive Local Health Security in Africa and India - Banda, Geoffrey; Mackintosh, Maureen; Njeru, Mercy Karimi; Makene, Fortunata Songora; Srinivas, Smita (International Political Economy Series,, 2024)
"This is a book whose time has come. Covid-19 should have forced a fundamental shift in thinking around the way African healthcare systems are organised, and how and where they procure essential health commodities. I recommend this book for every African policy maker, parliamentarian, opposition politician, financier, and especially for the political champions and civil servants in the Ministries of Health, Finance, Trade and Industry, Science and Education across the African continent." --Dr Skhumbuzo Ngozwana, President & CEO Kiara Health; Board Chairman Biovac; Board Member, Federation of African Pharmaceutical Manufacturers Associations, South Africa This open access edited volume focuses on the scope and benefits of strengthening local industrial-health linkages. The Covid-19 pandemic collapsed international supply chains for health. That experience brought home to African policy makers the critical nature of local manufacturing capabilities for sustaining and strengthening health care, and highlighted the pandemic benefits of India's much stronger industrial base. At that time, a network of researchers in East Africa, India and the UK were investigating how to address the crisis of cancer care in low-resource health systems. Their project, uniquely, focused on the scope and benefits of strengthening local industrial-health linkages. The project researchers were also drawn into the pressing demands of Covid19 response. The result is this very timely book. The authors link their research on cancer to pandemic experience, and they draw sharp lessons for how countries can enhance their populations' health security. The authors argue that improving cancer care is crucial for human wellbeing and more inclusive health care. They challenge policy makers to bring together health needs, health innovations and improved industrial capabilities to embed better cancer care and broader health system improvement in local industrial innovation and development. Geoffrey Banda is Senior Lecturer, Science Technology and Innovation Studies (STIS) Department, University of Edinburgh, UK Maureen Mackintosh is Emeritus Professor of Economics, Open University, UK Mercy Karimi Njeru is Research Scientist, Kenya Medical Research Institute (KEMRI), Kenya. Smita Srinivas is Founder, the Technological Change Lab and holds Visiting and Honorary Professorial appointments at the OU and UCL. Fortunata Songora Makene is Executive Director, Economic and Social Research Foundation (ESRF), Tanzania.